Sistem Pakar Mendiagnosis Penyakit Pada Ayam Broiler Menggunakan Metode Teorema Bayes Berbasis Web - Achmad Subana; R. Fanry Siahaan (Program Studi Teknik Komputer, Fakultas Teknik. Universitas Serambi Mekkah, 2021)
The need for chicken cannot be denied in Indonesian society, especially in the consumption of eggs and chicken meat so that it will affect economic growth. To produce healthy meat and eggs free of disease, breeders must pay attention to the health of their pet chickens. Starting from providing rations, vaccination and cage maintenance. Chicken disease is very susceptible to cage cleanliness and consumption of the food given. As for the scope of the problem in this study, namely disease in broiler chickens. The system used is a web-based expert system with the Bayes Theorem method. By applying the Bayes theorem method to expert systems in diagnosing broiler disease and designing an expert system application in determining broiler disease. Aims to assist breeders in dealing with diseases specifically broiler chickens and add to the list of references in applying the Bayes Theorem method to expert systems. Using testing with the PHP MYSQI application with the supporting tools.